Tunable Infrared Optics Enabled by Defect-Engineering of Vanadium Dioxide Using Focused Ion Beam - Wan, Chenghao; Rensberg, Jura; Zhang, Zhen; Hafermann, Martin; Mei, Hongyan; Xiao, Yuzhe; Salman, Jad; Ramanathan, Shriram; Ronning, Carsten; Kats, Mikhail A. (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
We demonstrate a simple method of spatially modulating the phase transition of vanadium dioxide using a focused ion beam (FIB). The modulated phase-transition characteristics were quantitatively analyzed, enabling a new platform for tunable infrared optics.
CRIS-Team Scopus Importer:2023-04-20